2004
DOI: 10.1182/blood-2003-09-3333
|View full text |Cite
|
Sign up to set email alerts
|

Immune activation set point during early HIV infection predicts subsequent CD4+ T-cell changes independent of viral load

Abstract: Although generalized T-cell activation is an important factor in chronic HIV disease pathogenesis, its role in primary infection remains poorly defined. To investigate the effect of immune activation on T-cell changes in subjects with early HIV infection, and to test the hypothesis that an immunologic activation "set point" is established early in the natural history of HIV disease, a prospective cohort of acutely infected adults was performed. The median density of CD38 molecules on CD4 ؉ and CD8 ؉ T cells wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
601
4
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 693 publications
(649 citation statements)
references
References 49 publications
(75 reference statements)
30
601
4
9
Order By: Relevance
“…1 Recently, it has been accepted that in addition to the direct infection of CD4 1 T lymphocytes by HIV virions, chronic immune activation in HIV-infected human and simian immunodeficiency virus (SIV)-infected non-natural hosts, such as rhesus macaques and cynomolgus macaques, may greatly contribute to the pathogenesis of AIDS. [2][3][4][5][6][7] Accumulated evidence suggests that large amounts of type I interferons (IFNs) produced by activated plasmacytoid dendritic cells (pDCs) might play a critical role in this chronic immune activation during HIV-1 infection. Clinical strategies aimed at inhibiting pDC activation could effectively counter disease progression in HIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 Recently, it has been accepted that in addition to the direct infection of CD4 1 T lymphocytes by HIV virions, chronic immune activation in HIV-infected human and simian immunodeficiency virus (SIV)-infected non-natural hosts, such as rhesus macaques and cynomolgus macaques, may greatly contribute to the pathogenesis of AIDS. [2][3][4][5][6][7] Accumulated evidence suggests that large amounts of type I interferons (IFNs) produced by activated plasmacytoid dendritic cells (pDCs) might play a critical role in this chronic immune activation during HIV-1 infection. Clinical strategies aimed at inhibiting pDC activation could effectively counter disease progression in HIV patients.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the tempo of HIV-and SIV-associated CD4 ϩ T-cell depletion is related to both the set-point level of viremia and the magnitude of virus-associated chronic immune activation (1,5). HIV/ SIV-associated chronic immune activation is characterized by polyclonal B-cell activation (6), high T-cell turnover of both CD4 ϩ and CD8 ϩ T cells with an enhanced cell surface expression of molecules indicative of cell activation (7), and high levels of circulating proinflammatory cytokines and chemokines (8).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies conducted by Golgi and colleagues concluded that excessive immune activation leads to immune dysfunction in chronic HIV patients. The findings showed that CD38 a maker of CD8 T cell and HLA-DR expression negatively correlate better with the worse condition of HIV infected persons than viral load [3][4][5]. So as CD4+ T-cell numbers decrease in HIV condition, HLA-DR+ and CD38+ CD8+ T lymphocytes rather appreciate in numbers [5].…”
Section: Open Access Http://scidocorg/ijmaiphpmentioning
confidence: 86%
“…However, the ratio of CD4/CD3 was significantly lower among treatment and treatment naïve HIV infected participants compared to control. The low level of CD4/CD3 exhibit a steady progression of the HIV infection [5,7] and is used to monitor some forms of immunodeficiency [4]. The association between low CD4+ T-cell count may possibly be explained by chronic inflammation in immunosuppressed HIV-infected individuals [21].…”
Section: Discussionmentioning
confidence: 99%